The role of intra- and interdialytic sodium balance and restriction in dialysis therapies - Lew, Susie Q.; Asci, Gulay; Rootjes, Paul A.; Ok, Ercan; Penne, Erik L.; Sam, Ramin; Tzamaloukas, Antonios H.; Ing, Todd S.; Raimann, Jochen G. (Frontiers in Medicine, 2023)
The relationship between sodium, blood pressure and extracellular volume could not be more pronounced or complex than in a dialysis patient. We review the patients’ sources of sodium exposure in the form of dietary salt intake, medication administration, and the dialysis treatment itself. In addition, the roles dialysis modalities, hemodialysis types, and dialysis fluid sodium concentration have on blood pressure, intradialytic symptoms, and interdialytic weight gain affect patient outcomes are discussed. We review whether sodium restriction (reduced salt intake), alteration in dialysis fluid sodium concentration and the different dialysis types have any impact on blood pressure, intradialytic symptoms, and interdialytic weight gain.